Comparative Analysis Of Lipid Profiles In Metabolic Syndrome Patients Before And After Lifestyle Intervention - Rashid, Hania; Munir, Khurram; Khan, Rida Ajmal; Jan, Fauzia; Ijaz Anwar, Muhammad; Fatima, Yamna (Journal of Neonatal Surgery, 2025)
Background: Metabolic Syndrome (Mets) is a set of diseases, such as high blood pressure, high blood sugar, too much body fat around the waist and irregular cholesterol levels, which put a person at risk of heart disease, stroke, and diabetes. Change in lifestyle is recommended to increase lipid profiles and decrease the risk of cardiovascular diseases. Purposes: To determine effects of lifestyle interventions on lipid profiles in MetS patients, with emphasis on changes in cholesterol, triglycerides and HDL levels. Study design: A prospective cohort study. Place and duration of study: Department of Biochemistry; Fazaia Medical College (FMC); Islamabad. Jan 2024 to July, 2024 Methods: The study was a prospective cohort study of patients with MetS who had lipid profile assessments at baseline and after a 12-week lifestyle intervention (dietary changes, physical activity, and behavior modification). Lipid profile was analyzed in blood samples collected at baseline and after the intervention. Results: The Mean age was 28.2 years (+- 10.4 years). The total cholesterol, LDL cholesterol and triglycerides were significantly decreased after the intervention (p=0.02, p=0.03 and p=0.01, respectively). There was a 8% HDL cholesterol increase (p=0.04), which shows the success of lifestyle changes in enhancing lipid profiles. Conclusion: Lifestyle interventions were found to significantly improve lipid profiles in MetS patients, and making dietary and physical activity changes is a way to adequately address cardiovascular risk factors..